Effect of murashige and skoog medium strength and plant growth regulators on the growth of Momordica cochinchinesis (gac fruit) - Grace, Ng Yun Ning (2025)
Momordica cochinchinensis, or Gac fruit, is a tropical superfruit known for its high nutritional and medicinal value but faces cultivation challenges such as low seed viability, poor germination, and environmental stress. Tissue culture offers a solution by enabling controlled propagation of elite plants. This study aimed to improve sterilization and optimize growth media for better in vitro propagation. Sodium hypochlorite concentrations for surface sterilization, Murashige and Skoog medium strengths, and cytokinin concentrations were evaluated for their role in affecting shoot growth and proliferation. Best surface sterilization was under 15% NaOCl for 10 minutes where 0% contamination rate was achieved, ensuring aseptic explant preparation. Among the tested MS medium strengths, full, half, and quarter, full-strength MS provided the best results, with the highest number of shoots (6.33 ± 0.33), shoot length (1.80 ± 0.06 cm), and leaf formation (4.67 ± 0.67) after five weeks. The study also tested various BAP concentrations (0, 1.0, 2.0, 3.0, and 4.0 mg/L), with 4.0 mg/L showing the highest shoot proliferation (16.67 ± 0.88), shoot length (4.50 ± 0.17 cm), and leaf number (12.00 ± 1.15), emphasizing the importance of hormonal optimization. The results highlight the significance of optimizing sterilization methods and media formulations to improve Gac fruit tissue culture efficiency, providing a foundation for sustainable cultivation and commercial production. Statistical analysis using One-Way ANOVA (p ≤ 0.05) showed that MS strength significantly affected all growth parameters, while BAP concentration significantly influenced shoot length but had no significant effect on shoot and leaf numbers.